OC-016 PROSPECTIVE DATA ANALYSIS OF 1307 VENTRAL HERNIA PATIENTS: EMERGENCY HERNIA REPAIR AND SMOKING PREDICT RECURRENCE. (13th October 2022) - Soppe, S F; Wirsching, A; Slieker, J; Keerl, A; Muller, M K; Nocito, A
Abstract: Aim: Ventral hernias are frequent and hernia repair is regularly performed by general surgeons. Emergency repair is less frequent and can be challenging. Long term data comparing outcomes of emergency- vs. elective ventral hernia repair are scarce. Material & Methods: Consecutive patients undergoing emergency and elective ventral hernia repair at our institution were prospectively entered in our HerniaMed database between August 2013 and February 2020. Patients were contacted after one-, five- and ten years to assess long-term complications. Risk factors for emergency repair and hernia recurrence were assessed by univariate and multivariate analysis. Results: We included 1307 patients. Emergency and elective hernia repair were performed in 11% and 89% of patients with one-year follow-op rates of 94% and 92%. Female gender, BMI >40 kg/m2, ASA class 3 and 4, large size umbilical herniation (>4cm) and epigastric herniation were more frequent in emergency hernia repair. Binary logistic regression analysis identified emergency repair and smoking as predictors of recurrence (Odds ratio: 4.04 and 95% confidence interval: 1.67–14.21, p=0.004; Odds ratio: 2.94 and 95% confidence interval: 1.33–9.15, p=0.011). Furthermore, female gender and significant comorbidity (ASA class 3 and 4) were risk factors for emergency repair (Odds ratio: 1.98 and 95% confidence interval: 01.05–3.74, p=0.034; Odds ratio: 3.54 and 95% confidence interval: 1.79–6.98, p<0.001). Conclusion: Emergency repair and smoking predicted hernia recurrence. Females and highly comorbid patients are at increased risk for emergency repair and should be prioritized for early elective hernia repair.